2008
DOI: 10.4137/bmi.s790
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Colorectal Cancer by Serum and Tissue Protein Profiling: A Prospective Study in a Population at Risk

Abstract: Colorectal cancer (CRC) is the second most common cause of cancer-related death in Europe and its prognosis is largely dependent on stage at diagnosis. Currently, there are no suitable tumour markers for early detection of CRC. In a retrospective study we previously found discriminative CRC serum protein profiles with surface enhanced laser desorption ionisation—time of flight mass spectrometry (SELDI-TOF MS). We now aimed at prospective validation of these profiles. Additionally, we assessed their applicabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…Additionally, differences may be due to differences in type of sample that was investigated; tissue vs. serum. Such a difference was also found by Engwegen et al ; a specific protein was lower in serum samples of colorectal cancer patients than in controls, while the same protein was higher in colorectal cancer tissue compared with healthy colon tissue of the same subjects (hyperplastic polyps) .…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, differences may be due to differences in type of sample that was investigated; tissue vs. serum. Such a difference was also found by Engwegen et al ; a specific protein was lower in serum samples of colorectal cancer patients than in controls, while the same protein was higher in colorectal cancer tissue compared with healthy colon tissue of the same subjects (hyperplastic polyps) .…”
Section: Discussionsupporting
confidence: 76%
“…This finding indicates no major difference in the immune activity or plasma biochemical composition between small and large polyps. Other studies present possible correlations between plasma proteins and polyp size [34,35]. Although there is evidence for correlation between immune activity and stage of colorectal cancer [10], to our knowledge, there is no similar evidence reported in the case of polyp size.…”
Section: Discussionmentioning
confidence: 74%
“…Wang et al identified two serum protein biomarkers (3961 and 5200 m/z) useful for monitoring colorectal cancer (Wang et al, 2009). Another recent study confirmed the decreased serum levels of apolipoprotein C-1 in CRC (Engwegen et al, 2008). Additionally, protein markers associated with lymph node metastases in colorectal and prostate cancer have been profiled (Pang et al, 2010;Fan et al, 2011).…”
Section: Discussionmentioning
confidence: 78%